PENGARUH PROMOSI, PROSEDUR KREDIT, TINGKAT SUKU BUNGA TERHADAP KEPUTUSAN NASABAH DALAM PENGAMBILAN KREDIT ULTRA MIKRO PADA PERUMDA BPR BANK GRESIK - Novita Devi Wulansari; Sukaris Sukaris (Pusat Riset dan Inovasi Nasional, 2021)
Unstable economic conditions during the pandemic resulted in several problems among Micro, Small and Medium Enterprises (MSMEs), namely a decrease in sales turnover to bankruptcy due to losses. The customer's decision to take credit is a process of selecting several alternative credit options after considering the related factors. Factors that influence customer decisions in taking credit at financial institutions include location, service, credit facilities, interest rates, credit terms and procedures and promotions. This study aims to determine the effect of promotions, credit procedures and interest rates on customer decisions in conducting ultra micro loans at PERUMDA BPR Bank Gresik. The research method used is quantitative method, with a population of 602 ultra micro credit customers at PERUMDA BPR Bank Gresik. The sample in this study used purposive sampling, namely the method of determining the sample with certain considerations. The sample used in this study were 86 respondents, the data collection technique used a questionnaire. The analysis technique uses multiple regression analysis. Promotion has a positive and significant effect on Customer Decisions in Taking Ultra Micro Credit. Credit Procedures have a positive and significant impact on Customer Decisions in Taking Ultra Micro Credit. Interest rates have a positive and significant effect on Customer Decisions in Taking Ultra Micro Loans.